1998
DOI: 10.1093/hmg/7.9.1417
|View full text |Cite
|
Sign up to set email alerts
|

Organization, expression and polymorphism of the human persyn gene

Abstract: Persyn is a recently identified member of the synuclein family with a distinct pattern of expression during pre- and postnatal development of the mouse peripheral and central nervous systems. As with other synucleins, persyn is believed to be involved in the pathogenesis of human neurodegenerative diseases. However, in contrast to other synucleins, high levels of persyn mRNA expression were also found in advanced breast carcinomas, suggesting an involvement of the encoded protein in breast tumour progression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 34 publications
1
73
0
1
Order By: Relevance
“…Sncg (also known as Persyn) is a small protein expressed in subsets of neurons and in carcinogenic breast and ovarian tissue believed to perform chaperone-like functions Ninkina et al, 1998;Bruening et al, 2000;Surguchov et al, 2001;George, 2002;Surgucheva et al, 2005). In the mouse retina, during development Sncg is regulated by the transcription factor Brn3b and expressed specifically in RGCs (Mu et al, 2004), and in the adult remains expressed in RGCs and not other retina cell types (Trimarchi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sncg (also known as Persyn) is a small protein expressed in subsets of neurons and in carcinogenic breast and ovarian tissue believed to perform chaperone-like functions Ninkina et al, 1998;Bruening et al, 2000;Surguchov et al, 2001;George, 2002;Surgucheva et al, 2005). In the mouse retina, during development Sncg is regulated by the transcription factor Brn3b and expressed specifically in RGCs (Mu et al, 2004), and in the adult remains expressed in RGCs and not other retina cell types (Trimarchi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Extraction of RNA from mouse tissues, Northern blotting, and preparation of labeled probes were carried out as described previously (7,36).…”
Section: Methodsmentioning
confidence: 99%
“…When overexpressed, SNCG stimulates proliferation and induces metastasis of breast cancer cells (22)(23)(24)(25)(26). Analysis of breast tumor samples did not identify any sequence variation of SNCG gene from its original normal neuronal environment and no gene amplification was detected either (27), suggesting that transcriptional activation could account for its abundant expression in breast cancer cells. By analyzing the promoter region of SNCG gene and conducting genomic sequencing, we had shown that the loss of methylation control in a CpG island located in exon 1 of SNCG was primarily responsible for the aberrant expression of this neuronal protein in breast carcinoma (28) and in some ovarian carcinomas (29).…”
Section: Introductionmentioning
confidence: 99%